Effect of total lunar eclipse of 27th July 2018 on the D-region ionosphere by using VLF observations. Issue 1 (1st January 2022) - Maurya, Ajeet Kumar; Phanikumar, D.V.; Singh, Rajesh; Venkatesham, K.; Singh, Abhay K.
Highlights: Total Lunar Eclipse of 27 July 2018 is investigated for its impact on lower ionosphere. Change in D-region electron density is inferred from VLF observations and modeling. Nighttime lower ionospheric density during the Total Lunar Eclipse was found to decrease. Abstract: In this report, an effort for the first time has been made to investigate the effect of the total Lunar Eclipse that occurred on 27th July 2018 (the longest lunar eclipse in the 21st century) on the D-region ionosphere. Very Low Frequency (VLF) navigational transmitter signals recorded at Prayagraj (formally Allahabad) station in India is the primary dataset used. The signals from two VLF transmitters: NWC (19.8 kHz) from Australia, and JJI (22.2 kHz) from Japan, have been utilized. When compared to unperturbed night, NWC signal amplitude showed an anomalous decrease of ∼0.86 dB, while JJI amplitude showed an anomalous increase ∼0.26 dB during the lunar eclipse. The Wait's lower ionospheric parameters: reflection height ( H' ) and sharpness factor ( β ) are estimated by using a rather coarse method of modeling of VLF signals anomalies on eclipse day, which comes out to be H'  = 85.25 km & β  = 0.689 km −1 and H'  = 84.59 km & β  = 0.683 km −1 respectively for NWC and JJI path. Using wait parameters, the electron density ( Ne ) profile is estimated and this showed a decrease in Ne during eclipse time with reference to the nighttime ambient values. The Ne values for the NWC path, showed relatively higher decrease compared to the JJI path. The plausible reasons for observed Ne decrease on lunar eclipse night could be due to the reflected lunar Lyman‐α and X-ray's radiation which may contribute to the nighttime ionization is blocked during the lunar eclipse, thereby decreasing the nighttime lower ionospheric Ne .